How do you multiply #-2w( w-3)(w+1)#?

1 Answer
Aug 15, 2015

Answer:

#=color(blue)(-2w^3 +4w^2 +6w)#

Explanation:

#-color(blue)(2w) * color(green)((w-3)) * color(red)((w+1))#

First multiplying the terms within the first two brackets.
#-color(blue)(2w) * color(green)((w-3))#

#=-color(blue)((2w)) * color(green)((w) -color(blue)((2w)) *(-3))#

#=-2w^2+6w# .
Now we multiply this expression with the term of the last bracket.

#=(-2w^2+6w) * color(red)((w+1))#

#=color(blue)((-2w^2) * (w) -(2w^2) * 1) + color(red)((6w)*(w) +(6w)*1#

#=-color(blue)(2w^3- 2w^2) + color(red)(6w^2 +6w)#

#=color(blue)(-2w^3 +4w^2 +6w)#